Role of the Advanced Practitioner in Leading Change in Primary Care. - Chishty, Qaiser Shahzad; Shashikant Bhasme (International Journal of Endorsing Health Science Research, 2023)
The role and recognition of advanced clinical practitioners (ACPs) have been subject to debate in various healthcare settings. Therefore, this review aims to critically analyze the role of ACPs in leading change within primary care services. By referring to current clinical research, the review aims to evaluate the efficacy of this role in creating a sustainable future for the National Health Service (NHS) by reducing the gap between primary and secondary care, as highlighted in the NHS Five Year Forward View. From the authors' perspective, the role of ACPs in leading change in primary care settings has never been more crucial than it is today. Understanding the changes that ACPs can introduce is essential to accelerate progress and achieve the most optimistic scenario for the future. However, the emergence of the ACP role faces three challenges: defining their domain, their training package, and determining the necessary adjustments in NHS organizations.